A cyan oxide fluorescent material that can be excited by purple light and a preparation method thereof

By using cyan oxide fluorescent material with the chemical formula Sr3-xEuxLu4-yScyGe5O19, and using Eu2+ activator to prepare under excitation of Unipox 405nm, the problem of lack of fluorescent materials suitable for excitation of Unipox LED chips in the prior art is solved, and an efficient full spectrum white LED device is achieved.

CN117568033BActive Publication Date: 2025-04-15XIAMEN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311560376.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2025-04-15
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

The prior art lacks oxide fluorescent materials that can have the main peak of the emission spectrum between 485 and 495 nm excitation under Unisex excitation and quantum efficiency of ≥70%, making it difficult to meet the demand for the multi-color fluorescent materials to achieve full-spectrum white LED devices.

Method used

A cyan oxide fluorescent material with the chemical general formula Sr3-xEuxLu4-yScyGe5O19 was used, where 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1 was used. Eu2+ was used as an activator to prepare high-temperature solid phase reaction under the excitation of 405 nm of Zengguang.

Benefits of technology

The main peak of the emission spectrum of fluorescent material under excitation of 405nm of Unisex light is achieved between 485 and 495nm, with a quantum efficiency of ≥70%, which is suitable for the application of white LED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117568033B_ABST
    Figure CN117568033B_ABST
Patent Text Reader

Abstract

A cyan oxide fluorescent material that can be excited by violet light and its preparation method, wherein the chemical composition of the fluorescent material is: Sr 3‑ x Eu x Lu 4‑y Sc y Ge5O 19 Where 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1. The crystal structure of the matrix corresponding to this material belongs to the hexagonal crystal system, with space group P6 / m. (The last part, "Eu," appears to be a fragment and doesn't translate directly. It likely refers to a specific crystal structure or matrix.) 2+ As an activator, when excited by violet light at 405 nm, the main peak of the emission spectrum of the cyan oxide fluorescent material that can be excited by violet light is located between 485 and 495 nm, with a quantum efficiency of ≥70%, thus enabling the fluorescent material to be applied to white LED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fluorescent materials, and in particular to a cyan oxide fluorescent material that can be excited by purple light and a preparation method thereof. Background Art

[0002] Phosphor-converted white LEDs (pc-wLEDs) have attracted much attention due to their high luminous efficiency, long life, environmental friendliness, and strong structure. The most common (traditional) pc-wLEDs are composed of a blue LED chip and a yellow phosphor (Y3Al5O 12 :Ce 3+ ) package, and the blue light emitted by the chip is combined with the yellow light emitted by the fluorescent material under the excitation of blue light to obtain white light. However, as stated in patent document 1 (Kevin James VICK, Gary Robert Allen, Ashfaqul Islam Chowdhury, Enhanced color-preference LED light sources using LAG, nitride and PFS phosphors, US10240087B2), the spectrum of this type of pc-wLEDs lacks cyan light (485-500nm wavelength range) and red spectrum, resulting in a low color rendering index (<70). With the continuous improvement of people's living standards, the requirements for lighting quality are getting higher and higher, and full-spectrum lighting has become a new trend. Compared with traditional pc-wLEDs, the spectrum of full-spectrum white light LEDs is close to the solar spectrum, the spectrum continuity is good, the spectrum distribution has no obvious peaks and troughs (especially there is no lack of cyan light), the color rendering index is excellent, and the ability to restore the color of objects is strong. It has a wide range of applications in the field of high-end lighting.

[0003] There are mainly two ways to realize full-spectrum white LEDs. The first is the splicing of multi-color chips, that is, combining multiple LED chips of blue, cyan, green, yellow, and red to produce a continuous spectrum. However, the control circuit of this method is complex and the cost is high. As an improved technical solution, such as the method disclosed in Patent Document 2 (Zhu Cheng, Zhang Zhihong, Li Yuyuan, Zhang Xiaoqing, He Minhui, Yuan Ruihong, Li Shengzhe, Wan Xihong, Lei Yuhou, Fluorescent glue with high color rendering index for white LEDs, its preparation method and LED packaging structure, CN110205085B), (the second solution) is to use a violet / ultraviolet LED chip to excite multi-color phosphors such as cyan, green, yellow, and red to obtain white light. Compared with the first method, this method has the advantages of stable light color, simple manufacturing method, low cost, etc., and thus has become the mainstream packaging method for full-spectrum white LEDs. However, due to concerns about possible leakage of (relatively harmful to the body) ultraviolet rays, the excitation of violet LED chips has received more attention. Therefore, the realization of full-spectrum white LEDs by exciting multi-color fluorescent materials based on violet LED chips has received the most attention, and the performance of violet LED chips is relatively stable. Developing fluorescent materials suitable for violet excitation and having excellent luminescence performance under violet excitation is gradually becoming a research hotspot in this field.

[0004] Currently, as reported in Non-Patent Document 1 (Chen Xiaoxia, Zhang Xia, Liu Ronghui, Liu Yuanhong, Zhou Yipeng, Zhuang Weidong, Development status and trend of phosphors for full-spectrum LED lighting, Engineering Sciences in China, 2020, 22(2):071-078), compared with luminescent materials of other colors, there are fewer varieties of cyan luminescent materials that can be excited by violet light and have excellent luminescence performance (high quantum efficiency, high thermal quenching performance, etc.). Patent Document 3 (Li Junhao, Kuang Meng, Jiang Wei, Zhang Qiuhong, Ni Haiyong, A sodium gadolinium gallium germanium garnet-based cyan phosphor and its preparation method, CN115368893B) discloses a Bi 2(1-x) Ga3Ge2O 12 :xBi 3+ -doped sodium gadolinium gallium germanium garnet-based cyan phosphor, where x is the doping concentration of Bi 3+ ions, 0 < x ≤ 0.20. This fluorescent material uses Bi 3+ as the luminescence center, can be excited by ultraviolet light with a wavelength of 260 - 380 nm, and emits a main peak at 480 nm. It should be noted that although the emission spectrum of this material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices and is not suitable for full-spectrum white LED devices realized by exciting multi-color fluorescent materials with violet LED chips.

[0005] Patent Document 4 (Shen Yufang, Liang Dongbao, Zhang Rui, A luminescent material, its preparation method and application, CN113930244A) also discloses a Bi 3+ ​​The doped material is a calcite-type crystal structure, a tetragonal system, and the chemical formula is BaLa 1-x Ga3O7:xBi 3+ Cyan gallate fluorescent material, wherein 0.05≤x≤0.13. The luminescent material can produce broadband excitation of cyan light of about 475nm under the excitation of 348nm near-ultraviolet light. It should be pointed out that although the emission spectrum of the material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices.

[0006] Similarly, patent document 5 (Huo Jiansheng, Zhou Jianbang, Li Junhao, Ding Jianhong, Ni Haiyong, a Bi 3+ Doped cyan phosphor and its preparation method, CN115011342B) also discloses a Bi 3+ Doped, chemical formula is Ba6Y 2- x Bi x Ga4O 15 Cyan fluorescent material, where 0.01≤x≤0.30. The main peak of the excitation spectrum of the fluorescent material is located at 340nm, and the main peak of the emission spectrum is located at 500nm (cyan light), covering the 400-650nm band. Similarly, although the emission spectrum of the material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices.

[0007] Similarly, patent document 6 (Shi Jianxin, Zhang Ziwang, Ye Zhibin, Li Zhuo, a Bi 3+ Doped cyan phosphor and its preparation method and application, CN116120927A) also discloses a Bi 3+ Doped, chemical formula Sr3In 2(y-x) Bi 2x(GeO4)3 cyan fluorescent material, wherein 0<x≤0.5, 1.02≤y≤1.05. The cyan fluorescent material has a garnet structure and good chemical stability. The main peak of its excitation spectrum is located at 415nm, covering the range of 365-450nm, and the main peak of its emission spectrum is located at 494nm, covering the range of 440-560nm. Obviously, the fluorescent material is highly compatible with the current commercial purple light chip, and is very suitable for purple light LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices. However, it should be pointed out that during the sintering process of the material, due to the volatility of In2O3 in the raw materials, a heating rate that is too fast will make the In raw material easier to sublimate, and a heating rate that is too slow will increase the overall heating time, and also cause the total amount of In raw material sublimation to increase, so the physical purity of the obtained fluorescent material is reduced. That is, it is difficult to synthesize the material, and it is difficult to obtain a pure phase material. The lower the purity of the fluorescent material, the lower its corresponding luminous intensity.

[0008] Similarly, patent document 7 (Jiao Huan, Wang Xiaoming, Yang Qingbo, A wide-spectrum cyan emission fluoride oxide phosphor and preparation method, CN116396756A) also discloses a Bi 3+ Doped, chemical formula is Na 1.45 La 8.55-x-y O 25.1 Si6F 0.9 :xBi 3+ / ySc 3+ A wide-spectrum cyan-emitting fluoride oxide fluorescent material, wherein 0.001≤x≤0.02; 0.01≤y≤0.05. The excitation spectrum of the wide-spectrum cyan-emitting fluoride oxide fluorescent material is 320-400nm, with the main peak at 350nm; the emission spectrum is 450-570nm, with the main emission peak at 497nm, emitting cyan light. Although the emission spectrum of this material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices. In addition, the material contains Na and F. Generally speaking, fluorides or (and) alkali metal compounds are more soluble in water or easily absorb water, which means that the chemical properties of the material are not stable.

[0009] Similarly, patent document 8 (Long Zhangwen, Qiu Jianbei, Zhou Dacheng, Wang Qi, A cyan phosphor excited by ultraviolet light and its preparation method, CN113004890B) also discloses a Bi 3+ Doped, chemical formula is Ca 3-x Ga 4-yO9: a cyan fluorescent material of xBi / yM1 / zM2, wherein M1 includes Zn and / or Ti, and M2 includes one or more of Li, Na, K, Rb and Cs; 0.01≤x≤0.3, 0≤y≤0.5, 0≤z≤0.3. Under the excitation of ultraviolet light with a wavelength of 365nm, the main peak of the emission spectrum of the material is located at ~480nm. Although the quantum efficiency of the material is ~100%, since its excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices.

[0010] From the above, we can see that Bi 3+ The luminescent performance of the doped cyan fluorescent material is not enough to satisfy the purple LED chip to excite the multi-color fluorescent material to realize the full spectrum white light LED device. Therefore, further, patent document 9 (Zeng Wei, Chen Xin, Lei Yutong, Mei Mengdi, Chen Wenxiao, A chlorosilicate cyan long afterglow luminescent material and its preparation method, CN116875302A) discloses a Eu 2+ Doped, chemical formula Sr 8-m-n SiO 12 Cl8:Eu m / R n Chlorosilicate cyan fluorescent material. Under the excitation of ultraviolet light with a wavelength of 350nm, the main peak of the emission spectrum of the material is located at ~480nm. At the same time, the material is a long afterglow material and is not even suitable for application in ultraviolet LED white light devices.

[0011] Similarly, patent document 10 (Pang Ran, Jiao Shengjian, Jiang Lihong, Wang Chaowei, Li Chengyu, Zhang Hongjie, a Eu 2+ Activated halogen-containing borate cyan phosphor and its preparation method and application, CN115287066B) also discloses a Eu 2+ Doped, chemical formula is Ba 6-x-y A y (BO3) 1-z (PO4) z X9:xEu 2+ Halogen borate cyan fluorescent material. The excitation spectrum of this material covers 300-400nm, reaches maximum excitation at 355nm, and the emission spectrum peak is at 470nm. Similarly, although the emission spectrum of this material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices.

[0012] Similarly, patent document 11 (Du Fu, Luo Wei, Zhou Yuqiang, Chen Chong, Zhang Wen, Divalent europium activated cyan phosphor and its preparation method and application, CN114702955A) also discloses a Eu 2+ doped, having a cubic spinel crystal structure and having the general chemical formula Mg 1-x-y R y Al 2-z D z O 4-m Q m :xEu 2+ A cyan fluorescent material, wherein R is at least one of Li, Na, and Zn, D is at least one of Ga, In, Y, and Sc, Q is at least one of N and F, and 0<x≤0.2, 0≤y≤0.2, 0≤z≤0.5, and 0≤m≤0.3. The excitation wavelength range of the cyan fluorescent material covers 250 to 400 nm, with the main peak at 330 nm; the peak wavelength of the emission spectrum is 460 to 510 nm. It should be pointed out that although the emission spectrum of this material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices.

[0013] Similarly, patent document 12 (Du Fu, Zhu Renwen, Zhang Wen, Cai Jinlan, Zhou Yuqiang, cyan phosphor and its preparation method, LED device, CN114921250A) also discloses a Eu 2+ Doped, chemical formula Sr 5-2y-x-z R y A y Ba x (PO4)3Cl:zEu 2+ A cyan fluorescent material, wherein 0<x≤2.5, 0.2≤y≤0.6, 0.2≤z≤0.5, R is selected from at least one of La, Gd, Lu, Y, and A is selected from at least one of Li, K, and Na. The excitation wavelength range of the cyan fluorescent material covers 250-450nm, with a main peak at 370nm, close to the purple range; the main peak of the emission spectrum is at ~470nm, close to cyan. Theoretically, the material is suitable for purple LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices. However, the material contains Na and F. Generally speaking, fluorides or (and) alkali metal compounds are more soluble in water or easily absorb water, which means that the chemical properties of the material are not stable.

[0014] Similarly, patent document 13 (Liu Quanlin, Shao Yuhe, Song Zhen, violet light excited chlorosilicate blue-cyan phosphor and preparation and application method, CN114605986B) discloses a violet light excited chlorosilicate blue-cyan phosphor with a chemical formula of M 4-x Eux R 2-y- z Ca y Si3O1 2-2z Cl 2z A chlorine-containing silicate blue-cyan fluorescent material, wherein M is Ba and Sr, and the molar ratio of Sr to Ba is greater than 0.01 and less than 0.15; 0.01 < x ≤ 0.20; R is Mg and Zn, and any molar ratio can be taken between the two elements; 0.8 < y ≤ 1.40; 0.01 < z ≤ 0.40. Under the excitation of ultraviolet light, the main peak range of the emission wavelength generated by this blue-cyan fluorescent material is between 450 and 495 nm. Obviously, this material is suitable for the ultraviolet LED chip to excite the multi-color fluorescent material to realize the full-spectrum white LED device. However, this material contains Cl. Generally speaking, chlorides (such as sodium chloride, calcium chloride) are more soluble in water or prone to absorb water, which means that the chemical properties of this material are not stable.

[0015] Similarly, Patent Document 14 (Zhang Jilin, Shi Rou, Lian Shixun, A highly efficient thermally stable divalent europium ion blue-green phosphor and its preparation method and application, CN115558493B) discloses a chemical general formula of Na a Ca b Al 11-c Mg c O 17+d :xEu 2+ A blue-green fluorescent material, wherein, 0.01 ≤ x ≤ 0.3, 0.5 ≤ a ≤ 3.5, 0 ≤ b ≤ 1.0, 0.1 ≤ c ≤ 1.5, 0 ≤ d ≤ 1.15. The excitation wavelength of this blue-green fluorescent material covers the range of 250 - 450 nm, and the main peak is located in the ultraviolet-near ultraviolet region, and it emits blue-green fluorescence with a peak located at 480 - 510 nm. Although the emission spectrum of this material is fully covered in the blue-green band, since the excitation spectrum is located in the ultraviolet region, it is only suitable for ultraviolet LED white light devices and is not suitable for the ultraviolet LED chip to excite the multi-color fluorescent material to realize the full-spectrum white LED device. In addition, this material contains Na. Generally speaking, alkali metal compounds are more soluble in water or prone to absorb water, which means that the chemical properties of this material are not stable.

[0016] Similarly, Patent Document 15 (You Hongpeng, Zhong Chuansheng, Yin Shuwen, A phosphor and its application, CN115109590B) discloses a trigonal crystal system, space group R3cH and chemical formula M a A b DE(PO4)6 blue-green fluorescent material, wherein, M is selected from Eu 2+; A is selected from one or more of Ca, Sr and Ba; D is selected from one or more of Li, Na and K; E is selected from one or more of Lu, La, Gd, Sc, Y and Ga; a and b parameters satisfy a+b=7 and 0.005≤a≤0.50. The material has broadband excitation in the range of 250-460nm, but the main peak is at 365nm; the main peak of the emission spectrum is at ~489nm, covering the visible light region of 425-675nm. Although the emission spectrum of this material fully covers the cyan band, since the excitation spectrum is in the ultraviolet region, it is only suitable for ultraviolet LED white light devices, and is not suitable for ultraviolet LED chips to excite multi-color fluorescent materials to achieve full-spectrum white light LED devices. In addition, the material contains Na. Generally speaking, alkali metal compounds are more soluble in water or easily absorb water, which means that the chemical properties of the material are not stable.

[0017] Similarly, Non-Patent Document 2 (Yuan Zhu, Lei Fu, Di Wu, Jiaqing Peng, Fu Du, Xinyu Ye, Lei Chen, Weidong Zhuang, A cyan-emitting phosphor Ca3SiO4(Cl,Br)2:Eu 2+ The cyan fluorescent material reported in the Journal of Luminescence (2021, 232:117854) also contains Cl (and Br). Generally speaking, chlorides (such as sodium chloride and calcium chloride) are more soluble in water or easily absorb water, which means that the chemical properties of the material are not stable. Non-patent document 3 (Sunggeun Shim, Woon Bae Park, Minseuk Kim, Jin-woong Lee, Satendra Pal Singh, Kee-Sun Sohn, Cyan-Light-Emitting ChalcogenometallatePhosphor, KGaS2:Eu 2+ , for Phosphor Converted White Light-Emitting Diodes, Inorganic Chemistry, 2021, 60(8):6047-6056) reported that the cyan fluorescent material is a more unstable (not water-resistant) sulfide (KGaS2:Eu 2+). The material reported in Patent Document 4 (Ming Zhao, Hongxu Liao, Maxim S.Molokeev, Yayun Zhou, Qinyuan Zhang, Quanlin Liu, Zhiguo Xia, Emerging ultra-narrow-band cyan-emitting phosphor for white LEDs with enhanced color rendition, Light: Science & Applications, 2019, 38) is Na 0.5 K 0.5 Li3SiO4:Eu 2+ , contains a large amount of Na / K / Li. Generally speaking, alkali metal compounds are more soluble in water or easily absorb water, which means that the chemical properties of this material are not stable.

[0018] In addition, patent document 16 (Wang Yuhua, Guo Haijie, Silicate long afterglow luminescent material and preparation method thereof, CN106497555B) and patent document 17 (Wang Yuhua, Guo Haijie, A cyan silicate ultra-long afterglow luminescent material and preparation method thereof, CN108949173B) respectively disclose a cyan silicate ultra-long afterglow luminescent material with a chemical formula of Ba 1-x-y ZrSi3O9:Eu x / R y Or Ba 1-x-y HfSi3O9:Eu x / R y (where 0<x≤0.05, 0<y≤0.05) and the chemical formula is Ba 2-m-n Zr 2-x-y Hf x Sn y SiO 12 :Eu m / R n (wherein, 0<m≤0.05, 0≤n≤0.05; 0≤x≤2, 0≤y≤2, 0≤x+y≤2; R=one or two of Tb, Ce, Dy, Tm, Nd, Gd, Y, Er, La, Pr, Sm, Yb, Lu, Ho). It should be pointed out that the long afterglow material will continue to emit light when the excitation stops. This means that even if the power is turned off, the LED light source will still emit light. Obviously, the long afterglow material is not completely suitable for white light LED lighting.

[0019] Non-patent document 5 (Mingzhang Liang, Jianfei Xu, Yaochun Qiang, Haojian Kang, Lulu Zhang, Jie Chen, Chun Liu, Xianbi Luo, Ying Li, Jingjing Zhang, Liqing Ouyang, Weixiong You, Xinyu Ye, Ce 3+ doped BaLu2Al2Ga2SiO 12 —A novel blue-light excitable cyan-emitting phosphor with ultra-high quantum efficiency and excellent stability for full-spectrum white LEDs, Journal of Rare Earths, 2021, 39(9):1031-1039) and Patent Document 18 (Qiang Yaochun, Ye Xinyu, You Weixiong, Liu Yanan, Xu Jianfei, Liu Shaopeng, Chen Jie, Tu Anna, Liang Heng, Liu Chun, A kind of aluminosilicate fluorescent material capable of emitting cyan light, CN112126433A) both disclose a garnet structure with the general chemical formula of BaLu 2-x CeAl2Ga2SiO 12 and M x Lu y Y z Ce a Al b Ga c Si x O 12 (wherein, M is at least one of Zn, Sr and Ba; x, y, z, a, b and c are molar coefficients, 0.2≤x≤1.2, 1.38≤y≤2.74, 0≤z≤0.2, 0.01<a≤0.12, 1.5≤b≤3.3, 1.0≤c≤2.5, and x+y+z+a=3, x+b+c=5) cyan luminescent material. However, it should be pointed out that the above materials are all silicates, rather than patent document 6 (Wang Xifeng, Xia Wei, Sun Peng, Effect of Surface Treatment on Performance of Silicate Phosphor for LED, China Powder Technology, 2014, 6:63-65) believes that due to the silicate system itself, the water resistance and high temperature and high humidity application performance of the fluorescent material have not been satisfactory, and it often needs to be coated to improve its water resistance and thermal quenching performance.

[0020] Patent document 19 (Xie Mubiao, A blue to cyan color-adjustable phosphor and its preparation method, CN104531143A) discloses a blue to cyan color-adjustable phosphor with a chemical composition of Ca 4-2x Li x Ce x Si2O7F2 fluorescent material; where x is the activation ion Ce 3+ Relative alkaline earth metal ion Ca 2+ The molar percentage coefficient is 0.001≤x≤0.10. 3+ As the ion doping concentration increases, the luminescent color of the fluorescent material gradually changes from blue to cyan. However, it should be pointed out that the material is fluorosilicate, which has poor water resistance and unstable chemical properties.

[0021] In conclusion, there is still a lack of oxide fluorescent materials with a main peak of emission spectrum between 485 and 495 nm and a quantum efficiency ≥ 70% under violet light excitation. 3-x Eu x Lu 4-y Sc y 5O 19 The cyan luminescence behavior (0.1≤x≤0.2, 0.5≤y≤1, the crystal structure of the corresponding matrix of the fluorescent material belongs to the hexagonal crystal system, and the space group is P6 / m) is disclosed for the first time in the present invention. Summary of the invention

[0022] To this end, the first object of the present invention is to provide a cyan oxide fluorescent material that can be excited by purple light. The crystal structure of the corresponding matrix of the material belongs to the hexagonal system, and the space group is P6 / m. 2+ As an activator, under the excitation of violet light of 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material that can be excited by violet light is located between 485 and 495nm, and the quantum efficiency is ≥70%.

[0023] To achieve the above object, the present invention adopts the following technical solution:

[0024] A cyan oxide fluorescent material that can be excited by violet light, the chemical formula of the material is:

[0025] Sr 3-x Eu x Lu 4-y Sc y 5O 19

[0026] Among them, 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1.

[0027] Preferably, x may be 0.15, and y may be 0.8.

[0028] The second object of the present invention is to provide a method for preparing a cyan oxide fluorescent material that can be excited by violet light. The preparation method comprises the following steps: subjecting a Sr precursor, a Eu precursor, a Lu precursor, a Sc precursor and a Ge precursor to a high-temperature solid-phase reaction under a reducing atmosphere to obtain a cyan oxide fluorescent material that can be excited by violet light.

[0029] Preferably, the molar ratio of Sr to Eu to Lu to Sc to Ge in the Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is (3-x):x:(4-y):y:5, wherein 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1.

[0030] Preferably, the Sr precursor is selected from one or more of Sr carbonates, Sr oxides, Sr oxalates and Sr nitrates; the Eu precursor is selected from one or more of Eu carbonates, Eu oxides, Eu oxalates and Eu nitrates; the Lu precursor is selected from one or more of Lu carbonates, Lu oxides, Lu oxalates and Lu nitrates; the Sc precursor is selected from one or more of Sc carbonates, Sc oxides, Sc oxalates and Sc nitrates; the Ge precursor is selected from one or more of Ge carbonates, Ge oxides, Ge oxalates and Ge nitrates.

[0031] Preferably, the purity of the Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is not less than 99.5%.

[0032] Preferably, the temperature of the high-temperature solid-phase reaction is 1400-1500° C., the atmosphere is a reducing atmosphere, and the time of the high-temperature solid-phase reaction is 4-10 hours.

[0033] Another object of the present invention is to provide a white light LED light source. The white light LED light source comprises a cyan oxide fluorescent material (corresponding to the chemical formula Sr 3-x Eu x Lu 4-y Sc y 5O 19 , where 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1) and a purple LED chip that can generate light between 380 and 420 nm.

[0034] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0035] Compared with the prior art, the method of the present invention can prepare a cyan oxide fluorescent material that can be excited by purple light. The chemical composition of the fluorescent material is: Sr 3-x Eu x Lu 4-y Sc y 5O 19 , where 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1. The crystal structure of the matrix of this material belongs to the hexagonal system, and the space group is P6 / m. 2+ As an activator, under the excitation of violet light of 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material that can be excited by violet light is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the emission spectrum of the material obtained in Comparative Example 1 under 405 nm excitation.

[0037] Figure 2 This is the X-ray diffraction pattern of the material obtained in Comparative Example 1.

[0038] Figure 3 This is the emission spectrum of the material obtained in Comparative Example 2 under 405 nm excitation.

[0039] Figure 4 This is the emission spectrum of the material obtained in Comparative Example 3 under 405 nm excitation.

[0040] Figure 5 This is the emission spectrum of the material obtained in Comparative Example 4 under 405 nm excitation.

[0041] Figure 6 This is the emission spectrum of the material obtained in Comparative Example 5 under 405 nm excitation.

[0042] Figure 7 This is the emission spectrum of the material obtained in Comparative Example 6 under 405 nm excitation.

[0043] Figure 8 The emission spectrum of the luminescent material obtained in Example 1 under 405nm excitation and the corresponding excitation spectrum.

[0044] Fig. 9 This is the emission spectrum of the luminescent material obtained in Example 14 under 405nm excitation.

[0045] Fig.10 This is the spectrum diagram of the white light LED device obtained in Example 19. DETAILED DESCRIPTION

[0046] The present invention provides a cyan oxide fluorescent material that can be excited by purple light, and its general chemical formula is as follows:

[0047] Sr 3-x Eu x Lu 4-y Sc y 5O 19

[0048] Among them, 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1.

[0049] In one embodiment of the present invention, x is preferably 0.1, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.11, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.12, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.13, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.14, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.15, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.16, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.17, and y is preferably 0.5; in one embodiment of the present invention, x is preferably 0.18, and y is preferably 0. 5; in one embodiment of the present invention, the x is preferably 0.19, and y is preferably 0.5; in one embodiment of the present invention, the x is preferably 0.2, and y is preferably 0.5; in one embodiment of the present invention, the x is preferably 0.15, and y is preferably 0.6; in one embodiment of the present invention, the x is preferably 0.15, and y is preferably 0.7; in one embodiment of the present invention, the x is preferably 0.15, and y is preferably 0.8; in one embodiment of the present invention, the x is preferably 0.15, and y is preferably 0.9; in one embodiment of the present invention, the x is preferably 0.1, and y is preferably 0.55; in one embodiment of the present invention, the x is preferably 0.1, and y is preferably 1; in another embodiment of the present invention, the x is preferably 0.2, and y is preferably 0.9.

[0050] The present invention also provides a method for preparing a cyan oxide fluorescent material that can be excited by violet light, the steps of which are as follows: mixing a Sr precursor, a Eu precursor, a Lu precursor, a Sc precursor and a Ge precursor, and performing a high-temperature solid-phase reaction under a reducing atmosphere to obtain a cyan oxide fluorescent material that can be excited by violet light.

[0051] In the above steps, the molar ratio of Sr, Eu, Lu, Sc and Ge in the Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is (3-x):x:(4-y):y:5, wherein 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1.

[0052] In the above steps, the Sr precursor can be a compound containing Sr well known in the art, and there is no special limitation. In the present invention, it is preferably one or more of Sr carbonate, Sr oxide, Sr oxalate and Sr nitrate, and more preferably Sr carbonate, i.e. SrCO3; the Eu precursor can be selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate, and more preferably Eu oxide, i.e. Eu2O3; the Lu precursor is selected from one or more of Lu carbonate, Lu oxide, Lu oxalate and Lu nitrate, and more preferably Lu oxide, i.e. Lu2O3; the Sc precursor is selected from one or more of Sc carbonate, Sc oxide, Sc oxalate and Sc nitrate, and more preferably Sc oxide, i.e. Sc2O3; the Ge precursor is selected from one or more of Ge carbonate, Ge oxide, Ge oxalate and Ge nitrate, and more preferably Ge oxide, i.e. GeO2.

[0053] The purity of the above-mentioned Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained fluorescent material.

[0054] In the above steps, the temperature of the high-temperature solid phase is preferably 1400-1500°C, and the atmosphere is a reducing atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1450°C; the reducing atmosphere can be a dry atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, a nitrogen-hydrogen mixed atmosphere with a volume ratio of 9:1 is preferred.

[0055] The high temperature solid phase time in the above steps is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0056] The high temperature solid phase reaction is preferably carried out in a high temperature furnace. After the reaction is carried out, the furnace is cooled to room temperature to obtain a cyan oxide fluorescent material that can be excited by purple light.

[0057] The embodiment of the present invention adopts a high temperature solid phase reaction to successfully prepare a cyan oxide fluorescent material that can be excited by purple light.

[0058] The present invention also provides a white light LED light source. The light source at least comprises a chemical formula of Sr 3-x Eu x Lu 4- y Sc y 5O 19(wherein, 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1) a cyan oxide fluorescent material that can be excited by violet light and an LED chip that can generate light between 380 and 420 nm. The specific production steps include: mixing a cyan oxide fluorescent material that can be excited by violet light (the present invention) with a green fluorescent material, a yellow fluorescent material, a red fluorescent material and an epoxy resin, applying the mixture to the surface of a violet LED chip that can generate light between 380 and 420 nm, and then curing the mixture at 150°C for 2 hours to obtain a white light LED light source.

[0059] In order to further illustrate the present invention, a cyan oxide fluorescent material that can be excited by purple light and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0060] The reagents used in the following comparative examples and embodiments are all commercially available.

[0061] Comparative Example 1

[0062] The raw materials are SrCO3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Lu, Sc and Ge in SrCO3, Lu2O3, Sc2O3 and GeO2 is 3:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace in a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr3Lu 3.5 Sc 0.5 5O 19 materials.

[0063] The fluorescent material obtained in Comparative Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 1 As shown. Since there is no Eu doping 2+ The material does not emit light at all under the excitation of violet light at 405 nm, as shown in Table 1. The material obtained in Comparative Example 1 was subjected to X-ray diffraction analysis using an X-ray diffractometer, and its diffraction pattern is as follows: Figure 2 As shown; the results of structural refinement show that the crystal structure of the oxide material (matrix) belongs to the hexagonal system and the space group is P6 / m.

[0064] Comparative Example 2 The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.95:0.05:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible, and sintered at 1450°C for 6h in a high-temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. The furnace is cooled to room temperature to obtain a theoretical chemical composition of Sr2.95 Eu 0.05 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0065] The fluorescent material obtained in Comparative Example 2 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 3 As shown. 2+ The doping concentration is low. Under the excitation of violet light at 405nm, the main peak of the emission spectrum of the material is located at 479nm, and the color is bluish. It can be seen that the material is not a cyan fluorescent material. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 2, and the quantum efficiency is 44.5%. See Table 1 for details. It can be seen that Comparative Example 2 is not a cyan oxide fluorescent material that can be excited by violet light.

[0066] Comparative Example 3

[0067] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.75:0.25:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.75 Eu 0.25 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0068] The fluorescent material obtained in Comparative Example 3 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 4 As shown. 2+ The doping concentration is relatively high. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the material is located at 501nm, and the color is green. It can be seen that the material is not a cyan fluorescent material. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 3, and the quantum efficiency is 50.3%. See Table 1 for details. It can be seen that Comparative Example 3 is not a cyan oxide fluorescent material that can be excited by violet light.

[0069] Comparative Example 4

[0070] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.9:0.1:3.6:0.4:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.9 Eu 0.1 Lu 3.6 Sc 0.4 5O 19 of fluorescent materials.

[0071] The fluorescent material obtained in Comparative Example 4 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 5 As shown. Since the x+y value does not fall within the range of 0.6 to 1.1, the main peak of the emission spectrum of the material under the excitation of 405nm purple light is located at 490nm. The material corresponding to Comparative Example 4 was tested for quantum efficiency using a quantum efficiency tester, and the quantum efficiency was 23.5%, which is on the low side. See Table 1 for details. It can be seen that Comparative Example 4 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of 405nm purple light, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, but its quantum efficiency is low, at only 23.5%, which makes it difficult to apply the fluorescent material to white light LED devices.

[0072] Comparative Example 5

[0073] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.9:0.1:2.9:1.1:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.9 Eu 0.1 Lu 2.9 Sc 1.1 5O 19 of fluorescent materials.

[0074] The fluorescent material obtained in Comparative Example 5 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 6As shown. Since the x+y value does not fall within the range of 0.6 to 1.1, the main peak of the emission spectrum of the material under the excitation of 405nm purple light is located at 492nm. The material corresponding to Comparative Example 5 was tested for quantum efficiency using a quantum efficiency tester, and the quantum efficiency was 18.7%, which is on the low side. See Table 1 for details. It can be seen that Comparative Example 5 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of 405nm purple light, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, but its quantum efficiency is low, only 18.7%, which makes it difficult to apply the fluorescent material to white light LED devices.

[0075] Comparative Example 6

[0076] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.8:0.2:2.9:1.1:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.8 Eu 0.2 Lu 2.9 Sc 1.1 5O 19 of fluorescent materials.

[0077] The fluorescent material obtained in Comparative Example 6 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 7 As shown. Since the x+y value does not fall within the range of 0.6 to 1.1, the main peak of the emission spectrum of the material under the excitation of 405nm purple light is located at 470nm, and the color is bluish. It can be seen that the material is not a cyan fluorescent material. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 6, and the quantum efficiency was 12.9%, which is low. See Table 1 for details. It can be seen that Comparative Example 6 is not a cyan oxide fluorescent material that can be excited by purple light, and the quantum efficiency is low.

[0078] Example 1

[0079] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.9:0.1:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.9Eu 0.1 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0080] The fluorescent material obtained in Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum and excitation spectrum. Figure 8 As shown. When the material is excited by 405nm purple light, the main peak of the emission spectrum is located at 485nm, and the main peak of the corresponding excitation spectrum is located at ~405nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 1, and the quantum efficiency was 70.2%. See Table 1 for details. It can be seen that Example 1 is a cyan oxide fluorescent material that can be excited by purple light. When excited by 405nm purple light, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0081] Example 2

[0082] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.89:0.11:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.89 Eu 0.11 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0083] The fluorescent material obtained in Example 2 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 485nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 2, and the quantum efficiency was 71.6%. See Table 1 for details. It can be seen that Example 2 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0084] Example 3

[0085] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.88:0.12:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.88 Eu 0.12 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0086] The fluorescent material obtained in Example 3 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 486nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 3, and the quantum efficiency was 72.4%. See Table 1 for details. It can be seen that Example 3 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0087] Example 4

[0088] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.87:0.13:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.87 Eu 0.13 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0089] The fluorescent material obtained in Example 4 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 487nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 4, and the quantum efficiency was 75.8%. See Table 1 for details. It can be seen that Example 4 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0090] Example 5

[0091] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.86:0.14:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.86 Eu 0.14 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0092] The fluorescent material obtained in Example 5 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 489nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 5, and the quantum efficiency was 76.1%. See Table 1 for details. It can be seen that Example 5 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0093] Example 6

[0094] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.85:0.15:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature with the furnace to obtain a theoretical chemical composition of Sr 2.85 Eu 0.15 Lu3.5 Sc 0.5 5O 19 of fluorescent materials.

[0095] The fluorescent material obtained in Example 6 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 490nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 6, and the quantum efficiency was 77.1%. See Table 1 for details. It can be seen that Example 6 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0096] Example 7

[0097] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.84:0.16:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.84 Eu 0.16 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0098] The fluorescent material obtained in Example 7 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 490nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 7, and the quantum efficiency was 77.3%. See Table 1 for details. It can be seen that Example 7 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0099] Example 8

[0100] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.83:0.17:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.83 Eu 0.17 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0101] The fluorescent material obtained in Example 8 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 492nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 8, and the quantum efficiency was 75.4%. See Table 1 for details. It can be seen that Example 8 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0102] Example 9

[0103] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.82:0.18:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.82 Eu 0.18 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0104] The fluorescent material obtained in Example 9 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 493nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 9, and the quantum efficiency was 72.1%. See Table 1 for details. It can be seen that Example 9 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0105] Example 10

[0106] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.81:0.19:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.81 Eu 0.19 Lu 3.5 Sc 0.5 5O 19 of fluorescent materials.

[0107] The fluorescent material obtained in Example 10 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 494nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 10, and the quantum efficiency was 70.9%. See Table 1 for details. It can be seen that Example 10 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0108] Embodiment 11

[0109] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.8:0.2:3.5:0.5:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.8 Eu 0.2 Lu3.5 Sc 0.5 5O 19 of fluorescent materials.

[0110] The fluorescent material obtained in Example 11 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 495nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 11, and the quantum efficiency was 70.3%. See Table 1 for details. It can be seen that Example 11 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0111] Example 12

[0112] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.85:0.15:3.4:0.6:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.85 Eu 0.15 Lu 3.4 Sc 0.6 5O 19 of fluorescent materials.

[0113] The fluorescent material obtained in Example 12 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 493nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 12, and the quantum efficiency was 70.4%. See Table 1 for details. It can be seen that Example 12 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0114] Embodiment 13

[0115] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.85:0.15:3.3:0.7:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.85 Eu 0.15 Lu 3.3 Sc 0.7 5O 19 of fluorescent materials.

[0116] The fluorescent material obtained in Example 13 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 492nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 13, and the quantum efficiency was 71.1%. See Table 1 for details. It can be seen that Example 13 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0117] Embodiment 14

[0118] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2, and the molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.85:0.15:3.2:0.8:5. After grinding and mixing, the above raw materials are put into a crucible, and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.85 Eu 0.15 Lu 3.2 Sc 0.8 5O 19 of fluorescent materials.

[0119] The fluorescent material obtained in Example 14 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Fig. 9As shown. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the material is located at 490nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 14, and the quantum efficiency was 80.1%. See Table 1 for details. It can be seen that Example 14 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0120] Embodiment 15

[0121] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.85:0.15:3.1:0.9:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.85 Eu 0.15 Lu 3.1 Sc 0.9 5O 19 of fluorescent materials.

[0122] The fluorescent material obtained in Example 15 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 488nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 15, and the quantum efficiency was 79.6%. See Table 1 for details. It can be seen that Example 15 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0123] Example 16

[0124] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.9:0.1:3.45:0.55:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.9 Eu 0.1 Lu 3.45 Sc0.55 5O 19 of fluorescent materials.

[0125] The fluorescent material obtained in Example 16 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 487nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 16, and the quantum efficiency was 72.5%. See Table 1 for details. It can be seen that Example 16 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0126] Embodiment 17

[0127] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.9:0.1:3:1:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.9 Eu 0.1 Lu3ScGe5O 19 of fluorescent materials.

[0128] The fluorescent material obtained in Example 17 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 485nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 17, and the quantum efficiency was 77.4%. See Table 1 for details. It can be seen that Example 17 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0129] Embodiment 18

[0130] The raw materials are SrCO3, Eu2O3, Lu2O3, Sc2O3, GeO2. The molar ratio of Sr, Eu, Lu, Sc and Ge in SrCO3, Eu2O3, Lu2O3, Sc2O3 and GeO2 is 2.8:0.2:3.1:0.9:5. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1450℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is Sr 2.8 Eu 0.2 Lu 3.1 Sc 0.9 5O 19 of fluorescent materials.

[0131] The fluorescent material obtained in Example 18 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of violet light 405nm was located at 485nm. The quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 18, and the quantum efficiency was 73.6%. See Table 1 for details. It can be seen that Example 18 is a cyan oxide fluorescent material that can be excited by violet light. Under the excitation of violet light 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material is located between 485 and 495nm, and the quantum efficiency is ≥70%, so that the fluorescent material can be applied to white light LED devices.

[0132] Embodiment 19

[0133] The cyan oxynitride fluorescent material (Sr 2.85 Eu 0.15 Lu 3.2 Sc 0.8 5O 19 ), green fluorescent material (β-sialon:Eu), yellow fluorescent material (Y3Al5O 12 :Ce), red fluorescent material (CaAlSiN3:Eu) and epoxy resin are mixed evenly in a mass ratio of 1:0.88:1.1:1.5:7, and the mixture is coated on a purple LED with a main peak of emission spectrum at 405nm, encapsulated, and then cured at 150℃ for 2h to obtain a white light LED light source with a color rendering index of 96.3. The spectrum of the obtained LED light source is tested using an LED spectrum tester, and its spectral distribution is as follows Fig.10 As shown, it can be seen that the continuity of the spectrum is good.

[0134] Table 1 Luminescence properties of materials corresponding to comparative examples and examples

[0135]

[0136] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by those familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.

Claims

1. A cyan oxide fluorescent material that can be excited by violet light, characterized in that: The chemical formula of the cyan oxide fluorescent material that can be excited by violet light is: Sr 3-x Eu x Lu 4-y Sc y 5O 19 , wherein 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.1; the crystal structure of the corresponding matrix of the cyan oxide fluorescent material that can be excited by violet light belongs to the hexagonal crystal system, and the space group is P6 / m; under the excitation of violet light of 405nm, the main peak of the emission spectrum of the cyan oxide fluorescent material that can be excited by violet light is located between 485 and 495nm, and the quantum efficiency is ≥70%.

2. A cyan oxide fluorescent material that can be excited by violet light as claimed in claim 1, characterized in that: The x is 0.15, and the y is 0.

8.

3. The method for preparing a cyan oxide fluorescent material that can be excited by violet light according to any one of claims 1 to 2, characterized in that: A Sr precursor, a Eu precursor, a Lu precursor, a Sc precursor and a Ge precursor are mixed, and a high-temperature solid-phase reaction is carried out in a reducing atmosphere to obtain a cyan oxide fluorescent material that can be excited by purple light.

4. The method for preparing a cyan oxide fluorescent material that can be excited by violet light as claimed in claim 3, characterized in that: The molar ratio of Sr, Eu, Lu, Sc and Ge in the Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is (3-x):x:(4-y):y:5, wherein 0.1≤x≤0.2, 0.5≤y≤1, and 0.6≤x+y≤1.

1.

5. The method for preparing a cyan oxide fluorescent material that can be excited by violet light as claimed in claim 3, characterized in that: The purity of the Sr precursor, Eu precursor, Lu precursor, Sc precursor and Ge precursor is not less than 99.5%.

6. The method for preparing a cyan oxide fluorescent material that can be excited by violet light as claimed in claim 3, characterized in that: The temperature of the high temperature solid phase reaction is 1400-1500° C., and the time of the high temperature solid phase reaction is 4-10 hours.

7. The method for preparing a cyan oxide fluorescent material that can be excited by violet light as claimed in claim 3, characterized in that: The Sr precursor is selected from one or more of Sr carbonate, Sr oxide, Sr oxalate and Sr nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Lu precursor is selected from one or more of Lu carbonate, Lu oxide, Lu oxalate and Lu nitrate; the Sc precursor is selected from one or more of Sc carbonate, Sc oxide, Sc oxalate and Sc nitrate; the Ge precursor is selected from one or more of Ge carbonate, Ge oxide, Ge oxalate and Ge nitrate.

8. A white light LED light source, characterized in that: The invention comprises a cyan oxide fluorescent material which can be excited by violet light as described in any one of claims 1 to 2 or a cyan oxide fluorescent material which can be excited by violet light obtained by the preparation method of any one of claims 3 to 7.

9. A white light LED light source as claimed in claim 8, characterized in that: It also includes a purple LED chip with an emission wavelength between 380 and 420 nm.

Citation Information

Patent Citations

  • Blue-to-cyan color adjustable fluorescent powder and preparation method thereof

    CN104531143A

  • Silicate long afterglow luminescent materials and their preparation methods

    CN106497555B

  • A cyan silicate ultralong afterglow luminescent material and its preparation method

    CN108949173B

  • Process for the extraction of metal ions

    EP0030067A1

  • Load ring for end face seal assembly

    EP0030085A1